Comparison of visual perceptual organization in schizophrenia and body dysmorphic disorder. Issue 1 (30th September 2015) - Silverstein, Steven M.; Elliott, Corinna M.; Feusner, Jamie D.; Keane, Brian P.; Mikkilineni, Deepthi; Hansen, Natasha; Hartmann, Andrea; Wilhelm, Sabine
Abstract: People with schizophrenia are impaired at organizing potentially ambiguous visual information into well-formed shape and object representations. This perceptual organization (PO) impairment has not been found in other psychiatric disorders. However, recent data on body dysmorphic disorder (BDD), suggest that BDD may also be characterized by reduced PO. Similarities between these groups could have implications for understanding the RDoC dimension of visual perception in psychopathology, and for modeling symptom formation across these two conditions. We compared patients with SCZ ( n =24) to those with BDD ( n =20), as well as control groups of obsessive–compulsive disorder (OCD) patients ( n =20) and healthy controls ( n =20), on two measures of PO that have been reliably associated with schizophrenia-related performance impairment. On both the contour integration and Ebbinghaus illusion tests, only the SCZ group demonstrated abnormal performance relative to controls; the BDD group performed similarly to the OCD and CON groups. In addition, on both tasks, the SCZ group performed more abnormally than the BDD group. Overall, these data suggest that PO reductions observed in SCZ are not present in BDD. Visual processing impairments in BDD may arise instead from other perceptual disturbances or attentional biases related to emotional factors. Highlights: Schizophrenia and body dysmorphic disorder may share perceptual organization impairments. This is the first direct comparison of these two disorders on perceptual organization. Only schizophrenia patients were characterized by impaired perceptual organization. The hyper-focus on detail in body dysmorphic disorder is likely due to other processes.